2021
DOI: 10.1007/s11764-020-00986-5
|View full text |Cite
|
Sign up to set email alerts
|

Important factors associated with sick leave after allogeneic haematopoietic stem cell transplantation—a 1-year prospective study

Abstract: Purpose This study examines sick leave (SL) and factors associated with full-time SL 1 year after allogeneic haematopoietic stem cell transplantation (allo-HSCT) in patients of working age from 2009 to 2016 (n = 122). Methods Questionnaire data were collected on admission to the allo-HSCT unit, at 7 months and 1 year after allo-HSCT. Associations between factors and SL were analysed using logistic regression analyses. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…This is consistent with previous research showing that health-related issues can delay a return to work, 21–24 with physical recovery occurring earlier than work recovery 22 . The ability to return to work is a sign of recovery for many allo-HSCT patients as it is perceived as a chance to return to normality, 42–44 but because of the severity of the treatment and subsequent adverse effects, most allo-HSCT survivors are on sick leave for long periods, with research showing that 1 year after allo-HSCT, 76% are still on either part- or full-time sick leave, 23 and 8 years after allo-HSCT, only 57% of survivors were back in full-time work or equivalent 24 . Early diagnosis of cGvHD together with treatment, evaluation, and the use of supportive care can alleviate complications and long-term conditions, 45 which may result in an improved work recovery for patients.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This is consistent with previous research showing that health-related issues can delay a return to work, 21–24 with physical recovery occurring earlier than work recovery 22 . The ability to return to work is a sign of recovery for many allo-HSCT patients as it is perceived as a chance to return to normality, 42–44 but because of the severity of the treatment and subsequent adverse effects, most allo-HSCT survivors are on sick leave for long periods, with research showing that 1 year after allo-HSCT, 76% are still on either part- or full-time sick leave, 23 and 8 years after allo-HSCT, only 57% of survivors were back in full-time work or equivalent 24 . Early diagnosis of cGvHD together with treatment, evaluation, and the use of supportive care can alleviate complications and long-term conditions, 45 which may result in an improved work recovery for patients.…”
Section: Discussionmentioning
confidence: 99%
“…Results also revealed that the prevalence of cGvHD at some point during the first year after allo-HSCT is associated with full-time sick leave 1 year after treatment. This is consistent with previous research showing that health-related issues can delay a return to work, 21–24 with physical recovery occurring earlier than work recovery 22 . The ability to return to work is a sign of recovery for many allo-HSCT patients as it is perceived as a chance to return to normality, 42–44 but because of the severity of the treatment and subsequent adverse effects, most allo-HSCT survivors are on sick leave for long periods, with research showing that 1 year after allo-HSCT, 76% are still on either part- or full-time sick leave, 23 and 8 years after allo-HSCT, only 57% of survivors were back in full-time work or equivalent 24 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…18 Chronic GVHD is a major fac tor influ enc ing RTW/sick leave, with one-quar ter of patients with chronic GVHD reporting being "dis abled/unable to work" at a median of 2 years post HCT. 16,19 Lower phys i cal func tion ing, multimorbidity, being female, and the receipt of periph eral blood stem cells for an unre lated HCT are asso ci ated with a lower like lihood of RTW post HCT. [20][21][22] A lack of stan dard guide lines for RTW lead ing to poor com mu ni ca tion between pro vid ers, patients, and employers can be a bar rier to suc cess ful rein te gra tion of patients in the work place after HCT.…”
Section: Social and Finan Cial Prob Lems After Hctmentioning
confidence: 99%